Bacillus velezensis A2 Can Protect against Damage to IPEC-J2 Cells Induced by Zearalenone via the Wnt/FRZB/β-Catenin Signaling Pathway - Jing Cai; Xuanshuai Yuan; Yuhang Sun; Jia Chen; Peng Li; Shuhua Yang; Miao Long (Toxins, 2024)
Zearalenone (ZEA) has adverse effects on human and animal health, and finding effective strategies to combat its toxicity is essential. The probiotic Bacillus velezensis A2 shows various beneficial physiological functions, including the potential to combat fungal toxins. However, the detailed mechanism by which the Bacillus velezensis A2 strain achieves this protective effect is not yet fully revealed. This experiment was based on transcriptome data to study the protective mechanism of Bacillus velezensis A2 against ZEA-induced damage to IPEC-J2 cells. The experiment was divided into CON, A2, ZEA, and A2+ZEA groups. This research used an oxidation kit to measure oxidative damage indicators, the terminal deoxynucleotidyl transferase-mediated nick end labeling (TUNEL) method to detect cell apoptosis, flow cytometry to determine the cell cycle, and transcriptome sequencing to screen and identify differentially expressed genes. In addition, gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) were adopted to screen out relevant signaling pathways. Finally, to determine whether A2 can alleviate the damage caused by ZEA to cells, the genes and proteins involved in inflammation, cell apoptosis, cell cycles, and related pathways were validated using a quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot methods. Compared with the CON group, the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) in the ZEA group increased significantly (p < 0.01), while the levels of antioxidant enzyme activity, total superoxide dismutase (T-SOD), glutathione peroxidase (GSH-PX), total antioxidant capacity (T-AOC), and catalase (CAT) decreased significantly (p < 0.01). Compared with the ZEA group, the A2+ZEA group showed a significant decrease in ROS and MDA levels (p < 0.01), while the levels of T-SOD, GSH-PX, T-AOC, and CAT increased significantly (p < 0.01). TUNEL and cell cycle results indicated that compared with the ZEA group, the A2+ZEA group demonstrated a significant decrease in the cell apoptosis rate (p < 0.01), and the cell cycle was restored. Combining transcriptome data, qRT-PCR, and Western blot, the results showed that compared with the CON group, the mRNA and protein expression levels of Wnt10 and β-catenin increased significantly (p < 0.01), while the expression level of FRZB decreased significantly (p < 0.01); compared with the ZEA group, the expression levels of these mRNA and proteins were reversed. Bacillus velezensis A2 can increase the antioxidant level, reduce inflammatory damage, decrease cell apoptosis, and correct the cell cycle when that damage is being caused by ZEA. The protective mechanism may be related to the regulation of the Wnt/FRZB cell/β-catenin signaling pathway.